Microstructural Synergy of ZrC-NbC Reinforcements and Its Coupled Effects on Mechanical and Dynamic Properties of Titanium Matrix Composites - Juan Wang; Haijun Zhang; Baiqing Zhou; Zhong Yang (Metals, 2025)
In aerospace applications, titanium matrix composites (TMCs) must balance high strength, thermal stability, and vibration resistance. This study investigates the microstructural evolution and multi-property correlations in single-phase ZrC-reinforced (TMC1) and dual-phase ZrC-NbC-co-reinforced (TMC2) TMCs via SEM/TEM, XRD, tensile testing, and ANSYS simulations. The in situ reaction (Ti + ZrC/NbC → TiC + Zr/Nb) and NbC-induced grain boundary pinning drive microstructural optimization in TMC2, achieving 30% higher reinforcement homogeneity and 5 μm grain refinement from 15 μm to 10 μm. TMC2’s tensile strength reaches 1210 MPa, a 15% increase over TMC1, with an elongation at a break of 4.74%, 2.2 times that of TMC1. This performance stems from synergistic Hall–Petch strengthening and nano-TiC dispersion strengthening. Modal simulations show TMC2 exhibits a first-mode natural frequency of 98.5 kHz, 1.1% higher than TMC1’s 97.4 kHz, with maximum displacement reduced by 2.3%. These improvements correlate with TMC2’s elevated elastic modulus (125 GPa vs. 110 GPa) and uniform mass/stiffness distribution. The ZrC-NbC synergy establishes a microstructural framework for the concurrent enhancement of static and dynamic properties, offering critical insights for a high-performance TMC design in extreme environments.